Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands. (17th March 2022) - Freeman, Benjamin W. J.; Evans, Chris D.; Musarika, Samuel; Morrison, Ross; Newman, Thomas R.; Page, Susan E.; Wiggs, Giles F. S.; Bell, Nicholle G. A.; Styles, David; Wen, Yuan; Chadwick, David R.; Jones, Davey L.
Abstract: Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of 2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation. Abstract : Peatlands are a globally important but diminishing and irrecoverable carbon store. Hydrology is a dominant driver of peatland ecosystem function, and water table depth is a strong predictor of peatland greenhouse gas emissions. Responsible management requires agriculture to adapt to the wetland character of peatlands. Wetland agriculture strategies could increase the resilience of production systems, deliver a wider range of environmental benefits and protect these valuable ecosystems for everyone's future benefit, whilst making a vital contribution to global climate change mitigation efforts.